(untitled) (Studia theodisca, 2012)
Following the footsteps of Horkheimer and Adorno’s Dialektik der Aufklärung, W. G. Sebald’s Die Ringe des Saturn develops a particular indictment of Enlightenment rationality, which manifests itself primarily as a critical examination of the three most prominent “scopic regimes” of the modern era: the “Cartesian Perspectivalism”, the “Descriptive paradigm” of Dutch seventeenth-century Art, and the “Baroque” visual culture. The critical exploration of these visual strategies stands in as representative for wide epistemological problems related to the rational ordering and organization of human thought and knowledge.